PTSL Wujud Pelaksanaan Kewajiban Pemerintah untuk Menjamin Kepastian dan Perlindungan Hukum Atas Kepemilikan Tanah - Susilaningsih, Tri (Jurnal Cakrawala Hukum, 2019)
Land registration is a government program in order to obtain legal certainty and legal protection for holders of land rights. While the process of making land certificates is considered slow so that it becomes the government’s attention, to overcome this problem, the government through the Ministry of Agrarian Affairs and Spatial Planning / Head of BPN launched the National Priority Program in the form of a Comprehensive Systematic Land Registration (PTSL). This research uses a normative- empirical study. Normative-empirical research is research conducted to examine normative legal rules in terms of its application. This normative-empirical study was carried out to examine how the implementation of PTSL is the Implementation of the Government’s Obligation to Ensure Legal Certainty and Protection of Land Ownership and what causes the slow pace of PTSL settlement as a Form of Implementation of the Government’s Obligation to Ensure Legal Certainty and Protection of Land Ownership. With the limited quantity and quality of Human Resources (HR) who deal with land registration a lot, with the implementation of PTSL, the implementation is experiencing obstacles so that the implementation of PTSL is not all smooth. PTSL acceleration goals are also not achieved on time.DOI: https://doi.org/10.26905/idjch.v10i1.3114.